Antibiotic-associated disorders of prothrombin synthesis and their probiotic correction with B. Clausii in breastfeed infants - O. G. Ivanko; O. V. Solianyk (Zaporožskij Medicinskij Žurnal)
The aim of the investigation was to study the prothrombin test and PIVKA-II serum levels changes in infants aged 1-6 month after the broad-spectrum antibiotic treatment and determine the possibility of coagulation disorders correction with the help of probiotic Bacillus clausii strains OC, NR, T, SIN spores capable to produce vitamin K2.